Efektivitas Model Numbered Head Together Berbantuan Media Kantong Bilangan Terhadap Pemahaman Konsep Perkalian SD - Nor Fatimah, Salsalia; Sutriyani, Wulan; Zumrotun, Erna (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
The purpose of the research is to determine the effectiveness and differences in increasing understanding of concepts before and after implementing the Numbered Heads Together learning model assisted by number bag media. Researchers used a Pre-Experimental approach. Meanwhile, the design uses a one-group pretest-posttest design. One-group pretest-posttest design is a type of research that uses a pretest and posttest after treatment, then compares the pretest and posttest scores. The research was conducted in Phase A class 2 of Jinggotan State Elementary School in the 2023/2024 academic year. The results of the research value increased by 100% above the KKM with an increase in the value of understanding the concept of multiplication before and after treatment with the Number Head Togather learning model with the help of number bag media with the average student pretest score being 40.06 with the lowest result being 23 and the highest result being 77. On the other hand, the posttest completion score was 78.88 with the lowest score being 73 and the highest score being 95. Based on the results of the paired sample t-test, the data significance value was 0.001 < 0.005. Thus, the application of the Number Head Together learning model by supporting number collection media is effective in understanding the concept of multiplication for grade 2 students at Jingotan State Elementary School. Kata Kunci: Number Head Togather, concepts understanding, number pocket media